MEMPERTIMBANGKAN METODE INTEGRALISTIK: Sosiologi untuk Kajian Islam dan Sosial - Zuly Qodir (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Social methods within sociology are varied based on the fact that society itself is not a single phenomenon. Social changes show various types of society based on how elements of society are constructed.. Positivisism, hermeneutics or verstehen and critics are among the popular methods within sosial theory. In the early period of sociology, positivisme became a dominant method used to explain social phenomena because there were strong assumption among the founder of sociology that this new discipline should be similar to natural sciences, which tried to reveal general law of social phenomena. The second period was marked by the massive use of hermeneutics within social theory. This leads to assumption that social phenomena are always developed in accordance to the needs of society. The next period of the development of sociology is dominated by the use of critics or postmodernism theory. This approach is mainly based on some essential critics on positivism. These different methodologies shows that social phenomenon is interpretable in many ways.